Exploring the Efficient Natural Products for the Therapy of Parkinson's Disease via Drosophila Melanogaster (Fruit Fly) Models. - Zhang, W.; Ju, Y.; Ren, Y.; Miao, Y.; Wang, Y. (Current Drug Targets, 2024)
Parkinson's disease (PD) is a severe neurodegenerative disorder, partly attributed to mutations, environmental toxins, oxidative stress, abnormal protein aggregation, and mitochondrial dysfunction. However, the precise pathogenesis of PD and its treatment strategy still require investigation. Fortunately, natural products have demonstrated potential as therapeutic agents for alleviating PD symptoms due to their neuroprotective properties. To identify promising lead compounds from herbal medicines' natural products for PD management and understand their modes of action, suitable animal models are necessary. Drosophila melanogaster (fruit fly) serves as an essential model for studying genetic and cellular pathways in complex biological processes. Diverse Drosophila PD models have been extensively utilized in PD research, particularly for discovering neuroprotective natural products. This review emphasizes the research progress of natural products in PD using the fruit fly PD model, offering valuable insights into utilizing invertebrate models for developing novel anti-PD drugs.